From MASLD to PAD: Looking for Cardiovascular Disease Starting from Metabolic Status - Andrea Boccatonda; Damiano D’Ardes; Veronica Moronti; Jessica Santilli; Alessia Cipollone; Gianfranco Lessiani; Nicoletta Di Gregorio; Carla Serra; Fabio Piscaglia; Claudio Ferri; Francesco Cipollone (Medicina)
Background: Peripheral artery disease (PAD) is still the least studied and evaluated form in clinical practice among atherosclerotic pathologies, despite the increased mortality and comorbidities related to it. The relationship between steatotic liver disease and an increased risk of cardiovascular disease has been extensively documented. Methods: The purpose of this work is to perform a review of the evidence linking NAFLD or MASLD to PAD, and examine possible clinical scenarios that arise from this new terminology. Results: The new definition of metabolic dysfunction-associated steatotic liver disease (MASLD) includes the presence of cardiometabolic risk factors and hepatic steatosis without any other underlying causes of hepatic steatosis; this terminology, coined in the hepatological field, could generate confusion, especially in the initial stages of its diffusion and among different medical specialists. Conclusions: Some recent data in the literature have strengthened the evidence of a pathological link between hepatic metabolic alteration (NAFLD or MAFLD) and PAD.